The Effect of Static Stretching Body Exercises in Increasing Hamstring Muscle Flexibility in Dancers at UKM Sangsekarta - Dwi Ayu Paramita; Safun Rahmanto; Rahim, Anita Farradila (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Indonesia cannot be separated from its diversity of arts and culture, including traditional dance. Dance is a work of art to express oneself through movements carried out by the body, therefore muscle flexibility is required in carrying out each movement in a dance. Flexibility, also known as flexibility, can affect the quality of movement in dancers. The hamstring muscles are one of the muscles that contribute to controlling body movements, whether practicing posture, running, jumping, or performing various kinds of dance movements. So training is needed to improve and maintain the flexibility of the hamstring muscles in dancers, one of which is by doing static stretching. Static stretching is often done by dancers, with the aim of training the dancer's physical endurance, muscle and bone strength, as well as helping to train breathing. The aim of this research is to determine the effect of providing static stretching body exercises in increasing hamstring muscle flexibility in dancers. This research design uses a pre-experimental design with a one group pre-test and post-test design. The sample for this research were dancers at UKM Sangsekarta, Muhammadiyah University of Malang. The sampling technique in this research used purposive sampling with a sample size of 27 people. The data measurement tool uses the Sit and Reach test. Data analysis tests were carried out using normality tests and hypothesis tests using SPSS. With the results of the pretest normality test being 0.074 (>0.05) and posttest 0.017 (<0.05) with the statement that the data is not normally distributed and the hypothesis test with a value of 0.00 (<0.05) with the statement that there is an influence. The conclusion in this study is that there is an effect of providing static stretching body exercise in increasing the flexibility of the hamstring muscles in dancers at UKM Sangsekarta.